Study of the Urban Street and Road Network for the Possibility of Allocating Lanes for Passenger Transport - Aleksey A. Tsarikov (Вестник СибАДИ)
Introduction. The existing traffic conditions in major Russian cities do not allow us to meet the high demand on the quality for passenger and cargo transportation. The speed of movement during peak hours decreases significantly and on some sections of the network corresponds to the pedestrian speed. The excessive volume of private transport movements requires the implementation of a set of measures aimed at the development of urban public passenger transport. One of these measures is the allocation of separate lanes for passenger transport. At the same time, the existing regulatory documentation recommends organizing such lanes only on sections of the road network with three or more lanes in one direction.The purpose of this work is to determine the proportion of the length of the street and road network of cities in which it is possible to organize lanes for public passenger transport without carrying out roadway reconstruction work.Materials and methods. Method of searching for the “conditional transport center” of the city proposed by the author was used in the process of writing the article. On order to divide the city territory, the method of concentric circles with a step of 1 kilometer was employed. Data on the number of traffic lanes on the road network of 17 cities in Russia and Eastern Europe were obtained applying the navigation system “Yandex. Maps”.Results. The data acquired as a result of the study showed that the share of the road network on which it is possible to allocate lanes for passenger transport can reach 40% or more. At the same time, the higher the population of a city, the greater the proportion of streets with multi-lane traffic. In the central part of the largest cities in Russia, the proportion of multi-lane streets reaches 60-80%. At the same time, as we move from the center to the periphery, the proportion of such highways gradually decreases to 10-15%.The formation of streets with multi-lane traffic was significantly influenced by the historical periods of cities’ development, as well as by the presence of tram traffic now and in the past.Discussion and conclusion. As a result of the research carried out, it can be concluded that in most Russian cities, the share of the street and road network on which it is possible to organize separate lanes for public passenger transport is slightly higher than the length of traffic jams. At the same time, in the largest cities, such as Yekaterinburg, the length of traffic congestion exceeded the share of multi–lane streets by 1.5 - 2 times. In cities with similar road conditions, the organization of dedicated traffic lanes for passenger transport is not enough to solve transport problems. In these cases, restrictive measures are needed to be implemented to reduce the use of personal automobile transport.